A multimodal meta-analysis of gray matter alterations in trigeminal neuralgia - Huang, Xiang; Li, Boyi; Li, Yuming; Lin, Junyu; Shang, Huifang; Yang, Jing (Frontiers in Neurology, 2023)
Background: Brain gray matter alterations in patients with trigeminal neuralgia (TN) have been detected in previous prior neuroimaging studies, but the results are heterogeneous. The current study conducted coordinate-based meta-analyses across neuroimaging studies, aiming to find the specific and commonpattern of brain anatomic and functional alterationsabnormalities in patients with TN.We performed a systematic literature search of PubMed, Embase and Web of Science to identify relevant publications. We conducted aA multimodal metaanalysis for whole-brain voxel-based morphometry (VBM) studies and functional imaging studies in TN was performed using anisotropic effect size-based signed differential mapping.The meta-analysis comprised ten VBM studies with 398 TN patients and 275 healthy controls, and thirteen functional magnetic resonance imaging studies with 307 TN patients and 264 healthy controls. The multimodal meta-analysis showed conjoint structural and functional brain changesalterations in the right fusiform gyrus and inferior temporal gyrus, bilateral thalamus, left superior temporal gyrus, left insula and inferior frontal gyrus. The unimodal meta-analysis showed decreased gray matter volume alone in the left putamen, left post-central gyrus, right amygdala; and only functional abnormalities in left cerebellum, bilateral precuneus and left middle temporal gyrus.This meta-analysis revealed overlapping anatomic and functional gray matter abnormalities in patients with TN, which may help provide new insights into the neuropathology and potential treatment biomarkers of TN.